Precise Modeling of Design Patterns in UML - Mak, Jeffrey K. H.; Choy, Clifford S. T.; Lun, Daniel P. K. (International Conference on Software Engineering: Proceedings of the 26th International Conference on Software Engineering; 23-28 May 2004, 2004)
Prior research attempts to formalize the structure ofobject-oriented design patterns for a more precisespecification of design patterns. It also allows automationsupport to be developed for user-defined design patternsin the future CASE tools. Targeting to a particular type ofautomation (e.g. verification of pattern instances),previous specification approaches over-specify patternstructures to a certain extend. Over-specification makespattern specification ambiguous and disallows thespecification language to be used for specifyingcompound patterns. In this paper, we present thestructural properties of design patterns which reveal thetrue abstract nature of pattern structures. To supportthese properties so as to solve the over-specificationproblem, we propose an extension to UML 1.5 (basicallyUML 1.4 with Action semantics). The specialization andrefining mechanism of UML provides also a smoothsupport for the instantiation, refinement and integrationof pattern structures specified in UML. Our work makesno significant extension to the UML 1.5 meta-model butmore in a UML Profile approach to ease the migration ofour work to UML 2.0, which has not yet officiallyreleased by OMG during this work.